The contribution of prostaglandin production to contractions of the isolated uterus of the rat - Vane, J. R. (1973)
1. Indomethacin and meclofenamate, both of which are potent inhibitors of prostaglandin synthetase, antagonized the contractor effects of oxytocin on the isolated uterus from the non-pregnant rat. Contractions induced by acetylcholine or prostaglandin F(2a) were not antagonized. 2. Uteri from rats 17-22 days pregnant exhibited intermittent spontaneous contractions when used as isolated preparations. They also released prostaglandin-like activity (mainly similar to F(2a)) into the bathing fluid. Both the prostaglandin release and the uterine activity were abolished by indomethacin. Activity could be restored by addition of low concentrations of prostaglandin E(2) or F(2a). 3. The release of prostaglandin F(2a)-like activity by the uteri increased dramatically on the expected day of delivery (day 22). 4. The results add force to the hypothesis that the spontaneous activity of some isolated organs is due to an intramural prostaglandin generation, and that increased uterine prostaglandin production contributes to the expulsion of the foetus.